Cadmium levels in high consumption fish from continental waters In the Province of los Ríos, Ecuador (Revista Científica Ciencias Naturales y Ambientales, 2019)
The concentration of Cd in the liver and muscle of Guanchiche (H. microlepis) and Dica (Pseudocurimata bolengeri) was determined. The concentration of the metal in the muscle tissue of the species is less than the limit of quantification of the method (
Keywords: Cadmium; Inland fish; Biometric variables; Haplias microlepsis; Pseudocurimata